1988
DOI: 10.1080/00150198808223235
|View full text |Cite
|
Sign up to set email alerts
|

Structure and phase transition in (CH3NH3)3Bi2Br9. A novel improper ferroelectrics

Abstract: The crystals of (CH,NH,),Bi,Br, have been grown which at room temperature are isomorphous with Cs,Bi,Br, and (CH,NH,),Sb,Br,.The space group is P3m1, a = 0.807, c = 1.008 nm, V = 0.5685 nm3, Z = 1 . The crystals reveal, when cooling, three phase transitions at 188f0.5, 140f1, and 101.5 f 0.5 K. The high temperature phase (I) behaves as a plastic one with respect to a freedom of rotation of methylammonium cations. The two high temperature transitions I+ I1 and II+ 111 can be related, similarly to (CH,NH,),Sb,Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(41 citation statements)
references
References 5 publications
2
39
0
Order By: Relevance
“…Around these transition temperatures the number of 81 Br NQR lines decreases stepwise with increasing temperature. The three transitions have been already reported by Jakubas et al [12]. The phases are named I, II, III, and IV in the order beginning with the room temperature phase.…”
Section: Tris-monomethylammonium Enneabromodibismuthate (Iii) (Ch 3 supporting
confidence: 53%
See 1 more Smart Citation
“…Around these transition temperatures the number of 81 Br NQR lines decreases stepwise with increasing temperature. The three transitions have been already reported by Jakubas et al [12]. The phases are named I, II, III, and IV in the order beginning with the room temperature phase.…”
Section: Tris-monomethylammonium Enneabromodibismuthate (Iii) (Ch 3 supporting
confidence: 53%
“…Therefore we could not decide about the exact number of NQR lines. Jakubas et al [12] reported the phase IV to be an improper ferroelectric; consequently, the crystal, phase IV, has no inversion center. We consider a lowering of the crystal symmetry from 2/m to m in phase IV; the space group of the structure may be Pm, from which eight 81 Br NQR lines can be expected for terminal bromines and four lines for the bridging Br atoms.…”
Section: / °mentioning
confidence: 99%
“…mononuclear) or extended (i.e. polynuclear) inorganic networks of corner-, edge-, or face-sharing octahedra, leading to an extensive family of bismuth halogenoanions (Jakubas, 1986;Jakubas et al, 1988Jakubas et al, , 1995. A variety of organic cations, ring shaped or linear, have a strong impact on the arrangements of BiX 6 octahedra and the formation of hydrogen bonds (Dammak et al, 2015;Elfaleh & Kamoun, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The interatomic Si--O distances ranging from 1.610 (4) to 1.662 (2) ~ are typical of this group and comparable with distances for other pyrosilicates (Batalieva & Patenko, 1967;Betechtin, 1950), and, especially Ba2CuSi207 (Malinovskij, 1984 Introduction. Solid alkylammonium halogenodiantimonates and -bismuthates are of interest because in some cases they show transitions to polar phases (Jakubas, 1986;Jakubas, Czapla, Galewski & Sobczyk, 1986;Jakubas, Sobczyk & Matuszewski, 1987;Jakubas, Krzewska, Bator & Sobczyk, 1988).…”
mentioning
confidence: 99%